2001
DOI: 10.1051/0004-6361:20010634
|View full text |Cite
|
Sign up to set email alerts
|

Properties of CSS radio sources from 102 MHz interplanetary scintillation observations

Abstract: Abstract. Interplanetary scintillation observations of 56 compact steep-spectrum radio sources have been carried out at 102 MHz on the Large Phased Array, Russia. Observations have shown that 42 sources have low-frequency cut-offs in their spectra. The physical conditions in the cores of the quasars and radio galaxies studied are estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The accuracy of this method is approximately an order of magnitude (for H ⊥ ) mainly due to the uncertainty of the measured angular size of the source (see details in Artyukh 1988, andTyul'bashev 2001). Using the above equation, magnetic fields have been calculated for approximately 50 sources with compact components and synchrotron self-absorption (Artyukh 1999;Tyul'bashev 2000;Tyul'bashev 2001;Tyul'bashev 2001a). However, there are only 5 cases for which H ⊥ could be estimated on both sides of the nucleus (Tyul'bashev 2000; Tyul'bashev 2001).…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of this method is approximately an order of magnitude (for H ⊥ ) mainly due to the uncertainty of the measured angular size of the source (see details in Artyukh 1988, andTyul'bashev 2001). Using the above equation, magnetic fields have been calculated for approximately 50 sources with compact components and synchrotron self-absorption (Artyukh 1999;Tyul'bashev 2000;Tyul'bashev 2001;Tyul'bashev 2001a). However, there are only 5 cases for which H ⊥ could be estimated on both sides of the nucleus (Tyul'bashev 2000; Tyul'bashev 2001).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In the absence of high spatial resolution data at low frequencies, the value for the magnetic field in 3C 268.3 (S) is doubtful and likely to be an overestimate (Tyul'bashev 2001). Apparently this large value of magnetic field can be explained by incorrect determination of the spectra maximum (H ∼ ν 5 ) or an incorrect value of the flux density at low frequency points.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In a sense, this paper is a proof-of-concept for the application of the IPS technique to flat-spectrum radio sources, which are expected to cause rather more difficulty in the estimation of total flux densities (S t ) at 111 MHz using such a method since they are, generally, much weaker (in S t ) than the steep-spectrum radio sources investigated earlier (Tyul'bashev& Chernikov 2001). We found that one-fourth (13 out of 48) of the flat-spectrum sources observed by us got estimates in S c that, in the worst scenario, have errors smaller than 35% (Table 3), with one exception at < 50%.…”
Section: Discussionmentioning
confidence: 98%
“…Flat spectrum sources are very difficult to detect at low frequencies (in total flux density), therefore the data reduction must be made with care (c.f. similar steep-spectrum radio source analysis in Tyul'bashev& Chernikov 2001). The data reduction method we used is given in Artyukh (1981) and Artyukh & Tyul'bashev (1996).…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…At its redshift of z ≈ 0.3695 (Boroson & Oke 1984) 3C 48 is one rare member of the class of compact steep spectrum (CSS) radio sources with a radio-spectral index α ∼ 0.9 (Tyul'bashev & Chernikov 2001). The quasar is rich in molecular gas, M H 2 ≈ 2.7 × 10 10 M , as CO(1-0) observations show (Scoville et al 1993;Wink et al 1997).…”
Section: Introductionmentioning
confidence: 99%